Distribution of finances taking into account statisticalinformation on the reliability of the items produced - Barketau, Maksim S. (Journal of the Belarusian State University. Mathematics and Informatics, 2025)
This paper examines the problem of distribution of finances among project contractors taking into account statistical information on the reliability of the items produced. Mathematical programming formulations necessary for constructing an optimal strategy of distribution are presented. To account for the influence of the spent amount of money on the number of component failures, it is proposed to build a linear or generalised linear regression, the coefficients of which are used in mathematical programming formulations.